If the Lord Is Willing and the Creek Don't Rise: Religious Attendance and Disaster Recovery in the Deep South*. (26th November 2018) - Bright, Candace Forbes; Hanks, Roma; Sayre, Edward; Broyles, Amye; Bagley, Braden
Abstract : Objective: This article examines the association between religious attendance and disaster recovery in Mississippi and Alabama. Methods: We use ordinary least squares regression to determine the effect of sociodemographic variables, social network size, and religious attendance on one's self‐described level of disaster recovery. Results: We find a robust association between frequent religious attendance and a greater level of recovery. Somewhat surprisingly, we also find a strong relationship between religious nonattendance and a greater level of recovery. However, these results differ by race. For whites (but not for blacks), nonattendance is associated with a greater degree of recovery, while for blacks (but not for whites), frequent attendance is correlated with a greater degree of recovery. For both whites and blacks, the size of one's social network does not affect disaster recovery. Conclusion: While according to previous research, religious attendance is associated with benefits based upon social networks and community engagement, we find that those who are strongly connected to their religious organizations recover more, but it is not directly connected to one's social network size.